Sign‐tracking modulates reward‐related neural activation to reward cues, but not reward feedback. (15th August 2022) - Duckworth, Jay J.; Wright, Hazel; Christiansen, Paul; Rose, Abigail K.; Fallon, Nicholas
Abstract: Research shows cognitive and neurobiological overlap between sign‐tracking [value‐modulated attentional capture (VMAC) by response‐irrelevant, discrete cues] and maladaptive behaviour (e.g. substance abuse). We investigated the neural correlates of sign‐tracking in 20 adults using an additional singleton task (AST) and functional magnetic resonance imaging (fMRI). Participants responded to a target to win monetary reward, the amount of which was signalled by singleton type (reward cue: high value vs. low value). Singleton responses resulted in monetary deductions. Sign‐tracking—greater distraction by high‐value vs. low‐value singletons ( H > L )—was observed, with high‐value singletons producing slower responses to the target than low‐value singletons. Controlling for age and sex, analyses revealed no differential brain activity across H > L singletons. Including sign‐tracking as a regressor of interest revealed increased activity ( H > L singletons ) in cortico‐subcortical loops, regions associated with Pavlovian conditioning, reward processing, attention shifts and relative value coding. Further analyses investigated responses to reward feedback ( H > L ). Controlling for age and sex, increased activity ( H > L reward feedback ) was found in regions associated with reward anticipation, attentional control, success monitoring and emotion regulation. Including sign‐tracking as a regressor of interest revealed increased activity in the temporal pole, a region related to value discrimination. Results suggest sign‐tracking is associated with activation of the 'attention and salience network' in response to reward cues but not reward feedback, suggesting parcellation between the two at the level of the brain. Results add to the literature showing considerable overlap in neural systems implicated in reward processing, learning, habit formation, emotion regulation and substance craving. Abstract : Using an additional singleton task and fMRI, participants responded to targets to win monetary rewards, the amount of which was signalled by singleton type (high value vs. low value). Singleton responses resulted in monetary deductions. Sign‐tracking—greater distraction by high‐value vs. low‐value singletons ( H > L )—was observed. Sign‐tracking correlated with increased BOLD response differentials across H > L singleton displays in regions associated with Pavlovian conditioning, reward processing, attention shifts and relative value coding. No such associations were found in response to reward feedback displays.